Pengaruh Disiplin Kerja dan Stres Kerja terhadap Tenaga Kesehatan di Puskesmas Kalidoni Kota Palembang - Kamilah, Dini Nurul; Hadjri, Muhammad Ichsan; Zunaidah, Zunaidah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of work stress on the performance of health workers at the Kalidoni Health Center in Palembang City. “The population in this study were all health workers at the Kaldioni Health Center in Palembang City with a sample of 38 people, using a saturated sampling technique. Saturated sampling technique is a sampling technique when all members of the population are sampled. Data obtained by distributing questionnaires to respondents. The analysis technique used is multiple linear regression analysis technique. The data was processed using the Statistical for Product and Service Solution (SPSS) program version 25. Based on the results of this study it shows that the work discipline variable has a positive and significant effect on performance, while the work stress variable has a negative and significant effect on performance, and work discipline and work stress as a whole together influence the performance of Health Workers at the Kalidoni Health Center in Palembang City. Keyword: Work Discipline, Work Stress, Performance